Gross anatomy of the gastrointestinal tract in reindeer, free-living and fed baled timothy silage in summer and winter - Aagnes, Tove H.; Mathiesen, Svein D. (Rangifer, 1996)
The gross anatomy of the gastrointestinal (GI) tract was investigated in reindeer calves (Rangtfer tarandus tarandus), free-living and fed two different qualities of timothy silage in September 1992 (summer) and April 1993 (winter) and related to the body condition. At both seasons nine male reindeer calves were taken from a natural pasture. Three animals were slaughtered directly (NP reindeer), three offered first cut (FC) silage and three regrowth (RG) silage ad lib., for 46 days. The FC silage contained 27% leaves and 57.8% dry matter (DM) cell wall content (CWC) and the RG silage 89 % leaves, and 38.7% DM CWC. The reticulo-rumen (RR) digesta wet weight in the NP reindeer in summer was 6.7-7.7% of body mass (BM), compared to 25.1-32.8% and 9.6-12.9% of BM, respectively, in the animals fed FC and RG silage. In winter the RR digesta wet weight relative to BM in the NP reindeer and in the animals fed FC and RG silages were 9-5-11.5%, 25.4-33.3% and 10.4-18.3%, respectively. The distal fermentation chamber (DFC) digesta wet weight in the NP animals in summer was 0.48-0.80% of BM, compared to 0.77-1.26% and 0.57¬0.65% of BM, respectively, in the animals fed FC and RG silage. In winter the DFC digesta wet weight relative to BM in the animals fed FC and RG silage did not differ significantly from the summer values (P>0.05), while in the NP reindeer it was 1.0-1.2% of BM which is significantly greater than in summer (P<0.05). The differences in relative weight of the fermentation chambers between the animals fed FC and RG silage both summer and winter were not reflected in total BM, which was similar in all groups fed silage. This is explained by a significantly lower carcass weight in the animals fed FC silage compared to the animals fed RG silage. Thus, the GI-tract gross anatomy in the silage fed animals seem to be highly affected by the plant structure and composition, and not by the season.